Individual and team competencies in translational teams. Issue 1 (21st October 2020) - Lotrecchiano, Gaetano R.; DiazGranados, Deborah; Sprecher, Jennifer; McCormack, Wayne T.; Ranwala, Damayanthi; Wooten, Kevin; Lackland, Daniel; Billings, Heather; Brasier, Allan R.
Abstract: Translational scientists create, advance, and translate knowledge as a result of research, learning, and application. Translational teams are composed of dynamic and diverse interprofessional and cross-disciplinary members that generate new knowledge to address a shared translational objective. The objective involves advancing an interventional product, behavioral intervention, or evidence-based approach to improve human health. This paper focuses on identifying individual and team competencies using a modified Delphi method to reach a consensus on the competencies needed by translational teams (TTs).